REGULASI EMOSI GURU PENDAMPING ANAK BERKEBUTUHAN KHUSUS DI SDIT INSAN QURANI SUMBAWA BESAR - Hikmah Khaerunnisa, Shabrina; Hakim, Lukmanul; Dwi Erliana, Yossy (JURNAL PSIMAWA, 2019)
This study aims to determine the emotional regulation of teacher with special needs students who have Qur'anic memorization in guiding and educating children with special needs. This research is a qualitative research with a descriptive approach. The subjects of this study were three accompanying teachers who had taught for more than 1 month at SDIT Insan Qur?ani Sumbawa Besar. Data analysis showed that two subjects (S and M) used memorizing Al-Qur'an as a medium to conduct effective emotional regulation for themselves. Especially subject S who showed better emotion regulation between the two other subjects seen from the cognitive and also emotional expressions that subject S showed when teaching in class. Meanwhile, subject D shows the opposite result. Subject D who has poor emotional regulation does not involve memorizing the Qur'an when feeling negative emotions. There are several factors that researchers found in the field that influence the regulation of emotions possessed by the three subjects namely mood / mood possessed by the subject, readiness to teach, physical condition of the subject while teaching, previous teaching experience, and the extent to which the subject is able to involve the Qur'an in regulating his emotions.